2019
DOI: 10.1155/2019/5456067
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Isolates and Drug Susceptibility Pattern of Sterile Body Fluids from Tertiary Hospital, Northern Ethiopia: A Four-Year Retrospective Study

Abstract: This study was conducted in Ayder comprehensive specialized Hospital, Mekelle, Northern Ethiopia, to determine the bacterial profiles and drug susceptibility pattern from body fluids. A total of 218 patients were investigated, of which 146 (67%) were males. The age of the study subjects ranged from 2 days to 80 years with 96(44%) in the age group of 15 years and above. The overall bacterial infection was 44 (20.2 %) of which gram positive bacteria were prevalent, 23 (52.3%) than gram negative bacteria 21 (47.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
20
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 17 publications
6
20
2
Order By: Relevance
“…According to this study, the major bacterial isolate in bloodstream infection among children is CoNS and K. pneumoniae which is similar to our previous report 38 and with others finding at northern 39 and central Ethiopia 40 42 . Nearly similar to a study in Egypt, Gabon and Zimbabwe where CoNS , E. coli and K. pneumoniae were the major isolates in bloodstream infection 43 45 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to this study, the major bacterial isolate in bloodstream infection among children is CoNS and K. pneumoniae which is similar to our previous report 38 and with others finding at northern 39 and central Ethiopia 40 42 . Nearly similar to a study in Egypt, Gabon and Zimbabwe where CoNS , E. coli and K. pneumoniae were the major isolates in bloodstream infection 43 45 .…”
Section: Discussionsupporting
confidence: 92%
“…Nearly similar to a study in Egypt, Gabon and Zimbabwe where CoNS , E. coli and K. pneumoniae were the major isolates in bloodstream infection 43 45 . In our finding, P. aeruginosa and K. pneumoniae are the major bacteria isolated from CSF unlike others report 5 , 38 , 41 , 46 . On the other hand, study from Tanzania has reported that S. aureus was the main pathogen in bloodstream infection unlike our finding 47 .…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Microbial agents that are associated with bloodstream infections may be modified via antibiotic administration and other factors specific to the patients such as surgical procedures, trauma, or underlying conditions, or by the quality of specimen collection, transport, and culture [46]. Reports of antimicrobial susceptibility patterns of bacterial isolates in body fluids are well documented in the literature worldwide and in the African settings but with varying outcomes [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial agents that are associated with bloodstream infections may be modified via antibiotic administration and other factors specific to the patients such as surgical procedures, trauma, or underlying conditions, or by the quality of specimen collection, transport, and culture [46]. Reports of antimicrobial susceptibility patterns of bacterial isolates in body fluids are well documented in the literature worldwide and in the African settings but with varying outcomes [46, 47]. In the present study, the bacterial isolates demonstrated varying resistance patterns to antibiotics ranging from low resistance to quinolones and fluoroquinolones (54/349 (15.5%)) and aminoglycosides (232/747 (31.1%)); moderate resistance to macrolides (149/357 (41.7%)) and cephalosporins (346/689 (50.2%)); and high resistance to tetracyclines (390/531 (73.4%)), penicillins (1282/1669 (76.8%)), and sulphonamides (450/499 (90.2%)).…”
Section: Discussionmentioning
confidence: 99%